2012
DOI: 10.1682/jrrd.2010.09.0188
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injury and posttraumatic stress disorder: Investigation of visual attention in Operation Iraqi Freedom/Operation Enduring Freedom veterans

Abstract: Abstract-Mild traumatic brain injury (mTBI) and posttraumatic stress disorder (PTSD) are prevalent dual impairments in veterans returning from the wars in Iraq and Afghanistan. Attention problems are a common self-reported complaint of veterans with mTBI, but relatively few studies have investigated the types and levels of behavioral attentional deficits present in veterans with mTBI and PTSD. The purpose of this study was to compare visual attentional performance between samples of veterans with both mTBI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…TBI as a result of blast injury has become increasingly prevalent in the last decade, but our understanding of its impact on functional and psychological outcomes remains limited. While some studies have demonstrated selective cognitive impairment resulting from blastrelated mTBI (Barlow-Ogden & Poynter, 2012), there are no consistent chronic neuropsychological deficits associated with blast-related mTBI greater than what is observed among individuals with non-blast-related mTBI (Belanger et al, 2009)-a finding that was replicated in the present study. Self-reported symptoms, on the other hand, are consistently elevated in veterans with TBI Levin et al, 2010) and suggest that sustaining blast-related mTBI is subjectively different than sustaining a civilian mTBI.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…TBI as a result of blast injury has become increasingly prevalent in the last decade, but our understanding of its impact on functional and psychological outcomes remains limited. While some studies have demonstrated selective cognitive impairment resulting from blastrelated mTBI (Barlow-Ogden & Poynter, 2012), there are no consistent chronic neuropsychological deficits associated with blast-related mTBI greater than what is observed among individuals with non-blast-related mTBI (Belanger et al, 2009)-a finding that was replicated in the present study. Self-reported symptoms, on the other hand, are consistently elevated in veterans with TBI Levin et al, 2010) and suggest that sustaining blast-related mTBI is subjectively different than sustaining a civilian mTBI.…”
Section: Discussionsupporting
confidence: 46%
“…However, the high prevalence of PTSD in blast-injured veterans makes it difficult to tease apart the unique effect of TBI versus the effect of PTSD on cognitive performance, given the body of research demonstrating the detrimental effects of PTSD on cognition (Dolan et al, 2012;Vasterling et al, 2012). Overall, although the majority of studies have suggested that blast-related mTBI does not lead to significant long-term cognitive impairment (e.g., Belanger et al, 2009;Vasterling et al, 2012), there does exist some evidence to the contrary (Barlow-Ogden & Poynter, 2012). Further, the complex pattern of long-term psychological symptom exacerbation (Belanger et al, 2011) associated with the blast injury mechanism complicates the ability to tease apart the effect of the blast-related mTBI versus the effect of the psychological sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of mTBI/PTSD have suggested impairments in aspects of executive functioning, including verbal fluency, response inhibition, and attention. [16][17][18] Recent studies looking more broadly at cognitive functioning differences between mTBI groups with or without PTSD failed to find differences between groups. 19,20 While these studies do not provide a consensus on the cognitive profile of patients with co-morbid mTBI/PTSD, it is clear that subjects with mTBI and co-morbid PTSD do not improve at the same rate as those with mTBI alone.…”
Section: Cognitionmentioning
confidence: 99%
“…4 TBI can result in diverse mental and physical sequelae that often are as unique to individual casualties as personality. 7,8 These include cognitive deficits, such as memory disorders, 9,10 attention loss, 11,12 and impaired executive functioning. 13 Mental health issues, such as post-traumatic stress disorder (PTSD) and depression, also are strongly associated with TBI, especially in combat.…”
Section: Introductionmentioning
confidence: 99%